Effects of the microalgae Chlamydomonas on gastrointestinal health. (February 2020) - Fields, Francis J.; Lejzerowicz, Franck; Schroeder, Dave; Ngoi, Soo M.; Tran, Miller; McDonald, Daniel; Jiang, Lingjing; Chang, John T.; Knight, Rob; Mayfield, Stephen
Graphical abstract: Highlights: Consumption of whole-cell Chlamydomonas reinhardtii biomass by mice and humans. C. reinhardtii significantly mitigated weight loss in a murine model of acute colitis. C. reinhardtii positively impacted gastrointestinal symptoms in humans. C. reinhardtii had no adverse effect on the microbial composition of participants. Abstract: The effects of consuming whole-cell biomass of the green algae Chlamydomonas reinhardtii on gastrointestinal health in mice and humans was examined. A 14-day murine model of acute colitis revealed significantly less weight loss in mice that received C. reinhardtii biomass by oral gavage. Based on this result, human volunteers with varying gastrointestinal symptoms were asked to consume 1 or 3 g of C. reinhardtii daily for 30 days. Participants reported changes in their gastrointestinal health through a questionnaire and provided stool samples to analyze the composition of their gut microbiome. Those who typically experience frequent gastrointestinal symptoms reported significantly less bowel discomfort or diarrhea, significantly less gas or bloating, more regular bowel movements, and better stool consistency when regularly consuming C. reinhardtii . Analysis of participant stool samples suggested the gut microbiome composition in all groups remained complex, and no signs of dysbiosis or adverse effect on microbial composition were observed.